Acute respiratory distress syndrome in patients with hematological malignancies. (1st May 2013) - Türkog˘lu, Melda; Erdem, Gökmen Umut; Suyanı, Elif; Sancar, Muhammed Erkam; Yalçın, Mehmet Muhittin; Aygencel, Gülbin; Akı, Zeynep; Sucak, Gülsan
<x xml:space="preserve">Abstract</x> Background: We investigated the clinical course and mortality of acute respiratory distress syndrome (ARDS) in patients with hematological malignancies. Methods: Sixty-eight patients with hematological malignancies and ARDS admitted to medical intensive care unit (ICU) of a university hospital were analyzed semi-prospectively in the study. Results: The most common etiology of ARDS was pneumonia. The ratio of partial pressure of oxygen in arterial blood to fractional concentration of inspired oxygen (PO2/FiO2) was 104 (74-165). Ten patients (15%) received non-invasive mechanical ventilation (NIV), 21 (31%) received invasive mechanical ventilation (MV), and 36 (53%) received both NIV and invasive MV. ICU mortality was 77% in the cohort. None of the variables with relevance to the underlying hematological disease was associated with mortality. The presence of two or more organ failures was the only independent risk factor for mortality (P = 0.045), whereas NIV was associated with low mortality (P = 0.001). The Kaplan-Meier curve of mortality, with respect to the type of MV support, demonstrated that NIV was associated with the lowest mortality (P < 0.001). Conclusion: The mortality of ARDS in critically ill patients with hematological malignancies is quite high. The presence of multi-organ failure is independently associated with high mortality whereas the use of NIV is independently associated with low mortality.